Meeting the Needs of Avid Book Readers: Access, Space, Concentration Support and Barrier Mitigation - Merga, Margaret (2017)
Â© 2017, Published with license by Taylor & Francis. Contemporary libraries perform multiple roles that greatly expand the scope of traditional service and resource provision. In order to determine how libraries can best meet the needs of avid book reading clientele, more needs to be known about their preferences of access and space, as well as barriers to their concentration and performance of sustained reading. Findings from the 2015 International Study of Avid Book Readers suggest that libraries should offer comfortable and quiet spaces conducive to reading for pleasure, that are responsive to the time, cost and concentration barriers that avid readers face, and not assume that avid readers will easily adapt to library environments with elevated noise levels.